Four Saccharomyces species differ in their tolerance to various stresses though they have similar basic physiological parameters - Zemančíková, Jana; Kodedová, Marie; Papoušková, Klára; Sychrová, Hana (Folia microbiologica, 2018)
Saccharomyces species, which are mostly used in the food and beverage industries, are known to differ in their fermentation efficiency and tolerance of adverse fermentation conditions. However, the basis of their difference has not been fully elucidated, although their genomes have been sequenced and analyzed. Five strains of four Saccharomyces species (S. cerevisiae, S. kudriavzevii, S. bayanus, and S. paradoxus), when grown in parallel in laboratory conditions, exhibit very similar basic physiological parameters such as membrane potential, intracellular pH, and the degree to which they are able to quickly activate their Pma1 H+-ATPase upon glucose addition. On the other hand, they differ in their ability to proliferate in media with a very low concentration of potassium, in their osmotolerance and tolerance to toxic cations and cationic drugs in a growth-medium specific manner, and in their capacity to survive anhydrobiosis. Overall, S. cerevisiae (T73 more than FL100) and S. paradoxus are the most robust, and S. kudriavzevii the most sensitive species. Our results suggest that the difference in stress survival is based on their ability to quickly accommodate their cell size and metabolism to changing environmental conditions and to adjust their portfolio of available detoxifying transporters.
Keywords: Stress, Physiological; Fermentation; Membrane potential; Intracellular pH; Glucose; Fungal Proteins; Stress tolerance; glukosa; Saccharomyces; protonové ATPasy; fungální proteiny; fyziologický stres; Proton-Translocating ATPases; fermentace